Parallel versus Twisted Pentacenes: Conformational Impact on Singlet Fission - Papadopoulos, Ilias; Reddy, S. Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Thiel, Dominik; Thoss, Michael; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of Physical Chemistry Letters, 2022)
We placed two pentacene chromophores at the termini of a diacetylene linker to investigate the impact of excitation wavelength, conformational flexibility, and vibronic coupling on singlet fission. Photoexcitation of the low-energy absorption results in a superposed mixture of states, which transform on an ultrafast time-scale into a spin-correlated and vibronically coupled/hot delocalized triplet pair 1(T1T1)deloc. Regardless of temperature, the lifetime for 1(T1T1)deloc is less than 2 ps. In contrast, photoexcitation of the high-energy absorption results in the formation of 1(T1T1)deloc lasting 1.0 ps, which then decays at room temperature within 4 ps via triplet-triplet annihilation. Lowering the temperature enables 1(T1T1)deloc to delocalize and vibronically decouple, in turn affording 1(T1T1)loc. In addition, our results suggest that the quasi-free rotation at the diacetylene spacer may lead to twisted conformations with very low SF quantum yields, highlighting the need of controlling this structural aspect in the design of new singlet fission active molecules.
CRIS-Team Scopus Importer:2023-03-07